Determinants of impaired coupling of right ventricle to hemodynamic load in advanced HFrEF. (3rd October 2022) - Melenovsky, V; Monzo, L; Benes, J; Reichenbach, A; Solar, N; Tupy, M; Jenca, D; Tykvartova, T; Miklovic, M; Al Hiti, H; Ters, J; Kautzner, J
Abstract: Background: The mechanisms and consequnces of impaired right ventricular (RV) dysfunction and impaired RV-pulmonary artery (PA) coupling in advanced heart failure (HF) poorely understood. Purpose: To compare RV-PA coupling parameters in patients with advanced HFrEF, PAH and in controls to ellucidate determinants and prognostic impact of RV-PA uncoupling in HFrEF. Methods: 260 pacients with advanced HF (NYHA 3.0±0.5, 40% CAD, LVEF: 23±10%, 87% males, BMI: 28±4.5 kg/m 2, BNP: 1238±982 pg/ml), 39 controls and 21 PAH patients underwent lab tests, ecocardiography, right heart catheterisation and equilibrium gated blood pool SPECT to precisely measure cardiac volumes. RV End-systolic elastance (Ees) and Effective arterial elastance (Ea) were calculated by single beat method. Patients were longitudinally followed for occurrence of adverse outcome (urgent Tx, LVAD or death without Tx/LVAD). Results: PAH patients had higher PA pressures and more dilated RV than HFrEF and controls. Despite of that, RV-PA coupling, reflected by Ees/Ea ratio, was more profoundly reduced in HFrEF than in PAH (Figure). While RV contractility (Ees) was augmented by increased afterload in PAH, such augmentation was absent in HFrEF. At follow-up (median 258; 53–763 days), 69% of HFrEF subjects experienced adverse event (17% death, 24% urgent HTx, 28% LVAD). In HFrEF, RV-PA coupling was strongly predictive od adverse outcome, more than RV EF%, RV EDV or RV Ees. The strongest predictors of reduced RV Ees/Ea ratio in HFrEF were in descending order: RV EF, RV EDV, PA systolic/systemic systolic pressure ratio (PAs/SBP), PAWP, heart rate, PA compliance, RA mean pressure, PA mean pressure, BNP level, SBP, PAs, Tri Reg grade, Non-CAD etiology of HF, Mi Reg grade, PVR, RV dyssynchrony, absence of ACEi/ARB/S-V (GLM model, all p<0.001). RV Ees/Ea ratio correlated with PAs/SBP ratio, that reflects systolic ventricular interdependence. Invasive PAs/SBP predicted outcome and closely correlated with non-invasive estimation of PAs/SBP. Conclusion: Despite having less PH and smaller RV, RV coupling is more impaired in HFrEF than in PAH due to absence of RV contractility enhancement. Higher RV volume, heart rate, tricuspid regurgitation, lower PA compliance, higher PAWP and systolic ventricular interdependence (PAs/SBP) are main determinants of RV PA decoupling in HFrEF. Elevated PA systolic pressure but low systemic BP (high PAs/SBP ratio) is associated with poor RV-PA coupling and prognosis. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): AZV NU20-02-00052, AZV NU21-02-00402